Дослідження скарбу срібників поблизу смт Городниця - Алфьоров, О.А.; Моця, Б.О.; Петраускас, А.В. (Археологія і давня історія України, 2021)
Срібники важливе джерело для вивчення давньоруської історії. Незначна кількість відомих на
сьогодні монет обумовлює високу увагу, яку вчені
приділяють кожній новій знахідці. В 2020 р. поблизу селища Городниця Новоград-Волинського району
Житомирської обл. було знайдено скарб давньоруських срібників. Місце знаходження було обстежено
експедицією Інституту археології НАН України,
яка виявила ще декілька монет. В статті аналізуються умови знаходження скарбу, можливості
його зв’язку із міськими населеними пунктами та
мережею комунікацій, наведено попереднє визначення монет. Minting own coin is one of the attributes of state
formation. The first coins of the Old Rus are represented
by gold and silver specimens dating from the late
tenth — early eleventh century. Gold coins are very
rare, the silver ones are presented much more.
Most modern researchers believe that the production
of silver coins was started by Volodymyr Sviatoslavych
and ended under Yaroslav Volodymyrovych
after the beginning of his reign in Kyiv. In 2020 the
third known hoard of silver coins was discovered near
Gorodnytsia village, Novohrad-Volynskyi district, Zhytomyr
region. It was found accidently by local resident
S. M. Komar who in the next day after discovery handed
it over to the authorities which was recorded in the
relevant documents.
The expedition of the Institute of Archaeology of the
National Academy of Sciences of Ukraine conducted archaeological
research at the hoard location. The place
where the silver coins have been occurred was recorded.
Several more coins were found in the pit where the hoard
was and nearby. Surrounding area was examined. Near
the hoard the presence of land- and waterways, which
functioned in the medieval period, was recorded. Near
the river Sluch there are convenient places for crossing.
During the exploration of the area adjacent to the
hoard in order to study the archaeological context the
settlement was discovered. The artifacts found on it
date it to the 9th—13th and 16th—18th centuries. Powerful
fortifications in the form of moats, ramparts and escarpments
have been preserved. Probably, the formation
of the silver hoard is connected with the ancient
roads along the Sluch River and the Old Rus settlement
on the site of the modern settlement of Gorodnytsia.
In total 38 silver coins were in the hoard. 31 of them
belonged to the minting of Volodymyr Sviatoslavych, and
7 to Sviatopolk Yaropolkovych. Vladimir’s coins are presented
in three types — II (6 copies), III (16 copies) and
IV (9 copies). Sviatopolk’s coins represent all three of his
existing numismatic types — I (4 copies), II (2 copies) and
III (1 copy). 10 silver coins of Volodymyr and 1 of Svyatopolk
are represented by previously unknown stamp
pairs. 2 coins of Vladimir, which have an unknown combination
of stamps, are of particular scientific interest.